2017
DOI: 10.1016/j.envpol.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Altered cellular metabolism of HepG2 cells caused by microcystin-LR

Abstract: This study aimed to evaluate the possible effects of microcystin-LR (MC-LR) exposure on the metabolism and drug resistance of human hepatocellular carcinoma (HepG2) cells. For this purpose, we first conducted an experiment to make sure that MC-LR could penetrate the HepG2 cell membrane effectively. The transcriptional levels of phase I (such as CYP2E1, CYP3A4, and CYP26B1) and phase II (such as EPHX1, SULTs, and GSTM) enzymes and export pump genes (such as MRP1 and MDR1) were altered by MC-LR-exposure for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…The results showed that the percentage of S-phase cells in the MC-LR-treated HBx 32 and HBx 4 groups was higher than that observed in the control group. An earlier study showed that treatment of HepG2 cells with MC-LR (0.1 nM to 10 µM) for 24 h did not affect HepG2 cell cycle and apoptosis (Ma et al, 2017(Ma et al, , 2018a. These in vitro results showed that the assayed MC-LR treatment concentrations and times were inadequate to affect the cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results showed that the percentage of S-phase cells in the MC-LR-treated HBx 32 and HBx 4 groups was higher than that observed in the control group. An earlier study showed that treatment of HepG2 cells with MC-LR (0.1 nM to 10 µM) for 24 h did not affect HepG2 cell cycle and apoptosis (Ma et al, 2017(Ma et al, , 2018a. These in vitro results showed that the assayed MC-LR treatment concentrations and times were inadequate to affect the cell cycle and apoptosis.…”
Section: Discussionmentioning
confidence: 71%
“…The observed effects of MC-LR and ctHBx on cell clone numbers in the present study showed that the MC-LR-treated HBx 32, HBx 4, and HBx groups exhibited increased levels of cell proliferation compared with the MC-LR-treated NC and HepG2 groups. Ma et al reported that the exposure of HepG2 cells to MC-LR (0.1 nM to 10 µM) for 48 h did not significantly affect cell proliferation (Ma et al, 2017(Ma et al, , 2018a. Studies have shown that exposure to low concentrations of MC-LR (0.01-100 nM) did not affect the viability of HepG2 cells and may be related to the tolerance of HepG2 cells to low concentrations of MC-LR (Jasionek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding to MC‐LR, there are several studies in the scientific literature in HepG2 cells but most of them used lower concentrations than in the present work as they were focused on the study of toxicity mechanisms and not in deriving EC 50 values (ie, Refs. ). Chong et al concluded that MC‐LR did not cause cytotoxic effects in HepG2 cells and other hepatic cell line in 48–96 h of exposure to concentrations up to 100 μg/mL.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, hepatocytes or hepatoma cell lines have been increasingly used as in vitro models to evaluate the toxicity of AA. Human hepatocellular carcinoma (HepG2) cells can display the morphology and biochemical activities of healthy hepatocytes and hence have been widely used to evaluate the toxic effects of various toxicants on hepatocytes for many years (van Ijzendoorn et al, 1997;Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%